Investigating agency in discourse :|multilingual Iranian immigrants in Istanbul - Sönmez, Elanur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis aims to provide a detailed examination of the agency construction of multilingual Iranian migrants living in Istanbul. Focusing on three Iranian women’s multilingual practices and daily experiences for one year, this linguistic ethnographic study explores the effect of different socio-political and personal factors in the agency construction of young Iranian women whose migratory movement is defined as lifestyle migration. The study investigates the concept of lifestyle migration in a relatively novel, non-Western context by comparing the experiences of the participants with the experiences of other lifestyle migrants. Participants observation supplemented with detailed fieldnotes along with the recordings of naturally occurring interactions and semi-structured interviews constituted the data set analyzed in this study. The findings suggest that the construction of agentive identities occur throughout different time spans and life events and these time spans expand into the past and present experiences and future plans of the individuals in an interlinked manner. All these factors operate hand in hand in order to shape and be shaped by the agentive actions of the individuals.
Keywords: Multilingual communication -- Iran.; Immigrants -- Turkey -- İstanbul.